2007
DOI: 10.1007/s10334-007-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of active contour model extensions for automated cardiac MR image segmentation by regional error assessment

Abstract: The developed regional error metric provided a more rigorous evaluation of the segmentation schemes in comparison to the classical derived parameters based on left ventricle volume estimation, usually used in functional cardiac MR studies. These derived parameters can furthermore mask local segmentation errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The active contour model can be classified into the edge-based models, which includes parametric models [17,18,19,20,21,22] and the geometric (or geodesic) models [14,23,24,25,26,27], and the region-based models [11,28,29]. This paper focuses on the parametric models and proposes a novel model to segment infrared images more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…The active contour model can be classified into the edge-based models, which includes parametric models [17,18,19,20,21,22] and the geometric (or geodesic) models [14,23,24,25,26,27], and the region-based models [11,28,29]. This paper focuses on the parametric models and proposes a novel model to segment infrared images more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…However, the endocardial contour is not smooth enough and the movement constraint based on image intensity for the snake is too empirical. Nguyen et al [25] compared the conventional snake, balloon snake and GVF snake on extracting the LV endocardium and concluded that the GVF snake has the best performance.…”
Section: Related Workmentioning
confidence: 99%
“…The other is necessary to use some training datasets, and is called segmentation with strong prior [8]. The examples of segmentation algorithms are thresholding [8,9], region growing [10], dynamic programming (DP) [11], deformable models [12], graph cuts [12], active contour models (ACM) [13][14], level-set [15], KNN classifier [16], convex relaxed distribution matching [17], robust adaptive Gaussian regularizing Chan-Vese (CV) model [18], and clustering [19]. Most of the previous works were focused on automatic LV segmentation for evaluating the cardiac function, but only a few works were focused on cardiac T2* estimation.…”
Section: Introductionmentioning
confidence: 99%
“…There are many previous works proposed as the methods for automatic segmentation in MR images which focus on different organs such as brain, kidneys, liver, and heart [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%